PENYELESAIAN SENGKETA ANTARA PT. ASTRA CREDIT COMPANIES DENGAN KONSUMEN DALAM PERJANJIAN LEASING - Fahreza Surya Sumantri, Hendro Saptono*), Marjo (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
Engagement is a term or expression which is abstract, which refers to the legal relationships in the field of wealth between two or more people or parties, where the legal relationship gave birth to one of the obligations of the parties involved in the legal relationship. Engagement born of the agreement is the most common in daily human life - today. This agreement will be undertaken where both parties have agreed or agreed to enter into this contract.The existence of the agreement as a source of engagement we can find its basis in Article 1233 Book of the Law - Civil Code which states that: